2018
DOI: 10.3329/bmrcb.v44i1.36798
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen: Class I Allele Frequencies and Haplotype Distributionin a Tertiary Care Hospital in Bangladesh

Abstract: Human leukocyte antigen (HLA) are cell surface glycoproteins encoded by Major Histocompatibility Complex (MHC) gene of human genome. HLA antigen frequency and haplotype distribution are useful for determining disease association, origin, migration and genetic relationship between populations and predicting the outcome of transplantation. Thus, the present study was carried out to identify HLA class I (HLA-A and HLA-B) antigen and haplotype distribution among a selected Bangladeshi population. This retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…In this study, among ESRD patients and donors, A, B and DRB1 locus were found to be similar and both groups were in genetic equilibrium found to be in agreement within both groups. Additionally, these highest frequent alleles were also be reported highest from a previous study, 10 as well as from another population based study from Bangladesh. 11 As cadaveric transplant has not yet started in Bangladesh, most of the donors of this study were blood relatives of the patients.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, among ESRD patients and donors, A, B and DRB1 locus were found to be similar and both groups were in genetic equilibrium found to be in agreement within both groups. Additionally, these highest frequent alleles were also be reported highest from a previous study, 10 as well as from another population based study from Bangladesh. 11 As cadaveric transplant has not yet started in Bangladesh, most of the donors of this study were blood relatives of the patients.…”
Section: Discussionsupporting
confidence: 64%